Asuhan Kebidanan Continuity Of Care (COC) Ny. A Dengan Hiperemesis Gravidarum Di Klinik Pratama Vina Kota Medan Provinsi Sumatera Utara - Normal Anita; Ida Ruhiya; Sihombing, Nurdelima; Karolin3; Salbiana; Marliani; Kismiasih (Medihealth: Jurnal Ilmu Kesehatan dan Sains, 2021)
810 women die due to pregnancy and childbirth. Between 2000 and 2017, the maternal mortality ratio (MMR, 305 maternal deaths per 100,000 live births) fell by approximately 38% worldwide, 94% of all maternal deaths occurring in low and middle income countries. Sub-Saharan Africa and South Asia accounted for about 86% (254,000) of the estimated global maternal deaths in 2017. Sub-Saharan Africa alone accounted for about two-thirds (196,000) of maternal deaths, while South Asia accounted for nearly one-fifth (58,000). Overall, the maternal mortality ratio (MMR) in developing countries has decreased to just under 50%. The Maternal Mortality Rate (MMR) is the ratio of maternal deaths during pregnancy, childbirth and childbirth caused by pregnancy, childbirth and childbirth or their management but not due to other causes such as accidents or incidentals in every 100,000 live births. In general, there was a decrease in maternal mortality during the 1991-2015 period from 390 to 305 per 100,000 live births. The number of maternal deaths by province in 2018-2019 where there was a decrease from 4,226 to 4,221 maternal deaths in Indonesia. In 2019 the most common causes of maternal death were bleeding (1,280 cases), hypertension in pregnancy (1,066 cases), infection (207 cases) details per province.